(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article examines the influence of linguistic ethics in arousing public sentiment. It explores the ethical considerations involved in using language to evoke emotions at a mass level and the potential impact on individuals and society. The study highlights the importance of responsible language use, empathy, and cultural sensitivity in shaping emotional responses. It also examines the role of media, advertising, and leadership in influencing public sentiment ethically. The article emphasizes the need for continuous reflection, dialogue, and improvement in linguistic ethics to foster positive emotional experiences and contribute to the well-being of society.